Nivolumab Enhances In Vitro Effector Functions of PD-1+ T-Lymphocytes and Leishmania-Infected Human Myeloid Cells in a Host Cell-Dependent Manner - Filippis, Christodoulos; Arens, Katharina; Noubissi Nzeteu, Gaetan Aime; Reichmann, Gabriele; Waibler, Zoe; Crauwels, Peter; van Zandbergen, Ger (Frontiers in Immunology, 2017)
Functional impairment of T-cells and a concomitant augmented expression of Programmed-Death-1 (PD-1) have been observed in visceral leishmaniasis patients, as well as in experimental models for visceral and cutaneous leishmaniasis. The PD-1/PD-1-Ligand (PD-1/PD-L) interaction negatively regulates T-cell effector functions, which are required for parasite control during leishmaniasis. The aim of this study was to elucidate the impact of the PD-1/PD-L axis in a human primary in vitro infection model of Leishmania major (Lm). Blocking the PD-1/PD-L interaction with nivolumab increased T-cell proliferation and release of the pro-inflammatory cytokines TNFα and IFNɣ during the co-cultivation of Lm-infected human monocyte-derived macrophages (hMDM) or dendritic cells (hMDDC) with autologous PD-1+-lymphocytes. As a consequence Lm infection decreased, being the most pronounced in hMDDC, compared to pro-inflammatory hMDM1 and anti-inflammatory hMDM2. Focusing on hMDDC, we could partially reverse effects mediated by PD-1 blockade by neutralizing TNFα but not by neutralizing IFNγ. Furthermore PD-1 blockade increased intracellular expression of perforin, granulysin and granzymes in proliferating CD4+-T-cells, which might be implicated in reduction of Lm-infected cells. In all, our data describe an important role for the PD-1/PD-L axis upon Lm infection using a human primary cell system. These data contribute to a better understanding of the PD-1-induced T-cell impairment during disease and its influence on immune effector mechanisms to combat Lm infection.